2017
DOI: 10.1371/journal.pone.0169676
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference in Multisensory Heading Estimation

Abstract: A large body of research shows that the Central Nervous System (CNS) integrates multisensory information. However, this strategy should only apply to multisensory signals that have a common cause; independent signals should be segregated. Causal Inference (CI) models account for this notion. Surprisingly, previous findings suggested that visual and inertial cues on heading of self-motion are integrated regardless of discrepancy. We hypothesized that CI does occur, but that characteristics of the motion profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 60 publications
13
70
0
Order By: Relevance
“…Our orientation relative to gravity can therefore be considered analogous to the heading of horizontal linear accelerations. Given that this premise is accepted, the present findings are similar to those of two recent studies on estimation of heading of translational motions in the horizontal plane [28,29]. Findings of the earlier study favored FF -although evidence for CI was found for one participant [28].…”
Section: Discussionsupporting
confidence: 90%
“…Our orientation relative to gravity can therefore be considered analogous to the heading of horizontal linear accelerations. Given that this premise is accepted, the present findings are similar to those of two recent studies on estimation of heading of translational motions in the horizontal plane [28,29]. Findings of the earlier study favored FF -although evidence for CI was found for one participant [28].…”
Section: Discussionsupporting
confidence: 90%
“…This variability could be interpreted as a sign that individuals are wired differently with respect to processes governing the formation of perceptions. However, we believe this to be unlikely: a similar variability has been reported in recent studies on the applicability of CI for perception of heading [20,21] and verticality [22]. As in the present study, it was found that different models were preferred over CI in individual cases, although in these studies the FF model was preferred in the majority of cases.…”
Section: Multisensory Distance Estimationsupporting
confidence: 87%
“…This formulation reflects the Model Averaging CI strategy (e.g., [18,28,29]). It is similar to earlier work by our group on heading estimation [20,30,21] and the perception of verticality [22]. The probability of a common cause given the sensory estimates is .…”
Section: Causal Inference Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…() observed subjects integrating visual and inertial information in heading estimation even under large spatial discrepancies (forced fusion). In a later study (de Winkel et al ., ), they did find evidence for causal inference models, which, however, also depended in a complex way on the specifics of the motion profiles (acceleration, maximum velocity, duration) of the stimuli.…”
Section: Models For Psychophysical Estimation and Judgment Paradigms:mentioning
confidence: 94%